2006
DOI: 10.1103/physrevlett.97.226802
|View full text |Cite
|
Sign up to set email alerts
|

First Principles Modeling of Tunnel Magnetoresistance ofFe/MgO/FeTrilayers

Abstract: By carrying out density functional theory analysis within the Keldysh non-equilibrium Green's functional formalism, we have calculated the nonlinear and non-equilibrium quantum transport properties of Fe/MgO/Fe trilayer structures as a function of external bias voltage. For well relaxed atomic structures of the trilayer, the equilibrium tunnel magnetoresistance ratio (TMR) is found to be very large and also fairly stable against small variations in the atomic structure. As a function of external bias voltage, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
84
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(96 citation statements)
references
References 25 publications
(28 reference statements)
9
84
0
Order By: Relevance
“…The competition between the rates of increase as a function of bias of the P majority and AP currents produces a rapid decay of the TMR, and we calculate V 1/2 being at around 0.7 V. The TMR peaks at zero bias where it reaches up to 290% but, because of its almost exponential decay, it approaches the mean value over the bias range investigated of 160% within only 0.2 V. All of these features are in good agreement with experimental data 15,28,29 and early theoretical results. 30,31 It is important to note also that, at very low bias voltages, the P minority current is slightly larger than the AP current. As it was shown by Rungger et al, 9 this large P minority current near the zero bias is due to the resonance of a Fe minority surface state through the MgO barrier and it is washed out as soon as a voltage is applied across the device.…”
Section: A Single-barrier Tunnel Junctionsmentioning
confidence: 99%
“…The competition between the rates of increase as a function of bias of the P majority and AP currents produces a rapid decay of the TMR, and we calculate V 1/2 being at around 0.7 V. The TMR peaks at zero bias where it reaches up to 290% but, because of its almost exponential decay, it approaches the mean value over the bias range investigated of 160% within only 0.2 V. All of these features are in good agreement with experimental data 15,28,29 and early theoretical results. 30,31 It is important to note also that, at very low bias voltages, the P minority current is slightly larger than the AP current. As it was shown by Rungger et al, 9 this large P minority current near the zero bias is due to the resonance of a Fe minority surface state through the MgO barrier and it is washed out as soon as a voltage is applied across the device.…”
Section: A Single-barrier Tunnel Junctionsmentioning
confidence: 99%
“…It was known that in the operational bias range the TMR ratio monotonically diminishes to zero for MgO based MTJs. 17 For MBP, we found that the spin injection and TMR ratio maintains a relatively large value and independent of a significant range of bias. We investigate physical properties of the spin injection efficiency, the tunnel magnetoresistance ratio, spin-polarized currents, charge currents and transmission coefficients as a function of external bias voltage, for two different device contact structures where MBP is contacted by Ni(111) and by Ni(100).…”
mentioning
confidence: 73%
“…An important device merit is the TMR ratio and much theoretical and experimental efforts have been devoted to create MTJs with different ferromagnetic metals and insulating materials in order to generate a large ratio. While materials such as MgO and Al 2 O 3 are the most popular barrier materials in practical MTJs, [16][17][18][19][20] 2D materials graphene 21,22 and transition-metal dichalcogenides 23,24 have also been investigated in this context.…”
mentioning
confidence: 99%
“…[36,37] Specifically, a linear combination of atomic orbitals (LCAO) is employed to solve KS equations. The exchange-correlation is treated at the LDA level and the nonlocal norm-conserving pseudopotential [38] is used to define the atomic core.…”
Section: Numerical Resultsmentioning
confidence: 99%